The high-temperature rotation-vibration spectrum and rotational clustering of silylene (SiH2). (May 2020) - Clark, Victoria H.J.; Owens, Alec; Tennyson, Jonathan; Yurchenko, Sergei N.
Highlights: A new ro-vibration line list for the electronic ground state silylene is presented. The line list is applicable for temperatures < 2000 K and covers range 0–10000 cm − 1 . A new spectroscopic PES and ab initio DMS of SiH2 were produced. Rotational energy level clustering in the spectrum of SiH2 has been investigated. Abstract: A rotation-vibration line list for the electronic ground state ( X ˜ 1 A 1 ) of SiH2 is presented. The line list, named CATS, is suitable for temperatures up to 2000 K and covers the wavenumber range 0–10 000 cm − 1 (wavelengths  > 1.0 µm) for states with rotational excitation up to J = 52 . Over 310 million transitions between  593 804 energy levels have been computed variationally with a new empirically refined potential energy surface, determined by refining to 75 empirical term values with J  ≤ 5 and a newly computed high-level ab initio dipole moment surface. This is the first, comprehensive high-temperature line list to be reported for SiH2 and it is expected to aid the study of silylene in plasma physics, industrial processes and possible astronomical detection. Furthermore, we investigate the phenomenon of rotational energy level clustering in the spectrum of SiH2 . The CATS line list is available from the ExoMol database (www.exomol.com ) and the CDS database.